The role of immunohistochemistry in the detection of vascular invasion in specimens of endoscopic submucosal dissection - Nayze Lucena Sangreman Aldeman; Daniel Moore Freitas Palhares; Stanley Almeida Araújo; Moisés Salgado Pedrosa; Luísa Lima Castro; Vitor Nunes Arantes; Mônica Maria Demas Álvares Cabral (Sociedade Brasileira de Patologia Clínica, 2013)
INTRODUCTION: Endoscopic submucosal dissection (ESD) of early neoplasias of the gastrointestinal tract (GIT) has been increasingly applied as an alternative to invasive surgical procedures, with the aim to preserve the patient's organ and quality of life, although it does not allow the histopathological analysis of lymph nodes. Previous studies demonstrated that the presence of neoplastic emboli in lymphatic (lymphatic vascular invasion [LVI]) or blood vessels (blood vascular invasion [BVI]) is considered a positive predictive factor for the occurrence of lymph node metastasis. The assessment of vascular invasion carried out only by routine hematoxylin and eosin staining (HE) may yield both falsepositive and false-negative results. D2-40 is a specific monoclonal antibody to the lymphatic endothelium. Thus, it is useful for identifying LVI and distinguishing if tumor embolization is found in blood or lymphatic vessels. OBJECTIVE: To determine the role of immunohistochemistry (IHC) in the assessment of ESD specimens by comparing the detection of LVI and BVI by HE and IHC with D2-40 and CD34 immunolabeling. METHOD: We conducted the IHC study using D2-40 and CD34 markers (pan-endothelial) in 30 cases of ESD with histological diagnosis of carcinoma in order to assess the presence of LVI and BVI. RESULTS: The detection of LVI was more prevalent than BVI. Three out of six cases with LVI were false-positive by HE and six were false-negative by IHC. Regarding BVI, five cases were identified and one was false-negative by IHC. CONCLUSION: Our results indicated that the histopathological analysis of ESD specimens by exclusively routine HE staining does not allow proper evaluation of BVI or LVI.